Legal Perception and Finance: The Case of IPO Firm Value. (14th June 2021) - Schnyder, Gerhard; Grosman, Anna; Fu, Kun; Siems, Mathias; Aguilera, Ruth V.
Abstract: In this paper, we contribute to the literature on institutional determinants of IPO valuation. We introduce the concept of 'legal signalling', which focuses on the perception of the quality of law and thus complements the existing institutional approaches to IPO valuation which consider the quality of the positive law ('standard view') and firm‐level corporate governance practices ('firm signalling view'). Our approach explicitly models the difference between the effect of the positive law and the effect of the perception of law on IPO value. Based on a worldwide longitudinal dataset of IPO performance across a large number of countries, we find strong support for the claim that the perception of the quality of law is more important than its actual quality to explain post‐IPO firm value. This effect holds regardless of whether the law's quality is correctly perceived or misperceived. Overall, our findings underscore the need for a more sophisticated theorization of the ways in which law affects entrepreneurial finance.